Active suspension system with integrated electrical tubular linear motor: design, control strategy and validation - Thul Andreas; Eggers Daniel; Riemer Björn; Hameyer Kay (Archives of Electrical Engineering, 2015)
This paper focuses on the design and control of an active suspension system, where a tubular linear motor is integrated into a spring damper system of a vehicle. The spring takes up the weight of the vehicle. Therefore the electric linear motor can be designed very compact as it has to provide forces to adjust the damping characteristic only. Design and construction of the active suspension system, a control strategy and validation measurements at a test bench are presented.